Mapping Natural Resource (weather, soil, water, crop vegetation) to Identify Hotspots in Morocco - Devkota, Krishna; Atassi, Layal; Devkota Wasti, Mina Kumari (International Center for Agricultural Research in the Dry Areas, 2022)
Hotspot mapping using real-time geospatial information of climate, soil, water, and vegetation indices provides a guideline for developing appropriate agricultural practices and policies and strategies for sustainably utilizing natural resources, implementing adaptation strategies, and optimization of the production resources in agriculture. OneCGIAR Initiative F2R-CWANA WP3 mapped natural resources (climatic parameters, water, soil, and vegetation indices) in Central and West Asia and North Africa (CWANA) region country, Morocco. Climatic variables used for mapping include long-term rainfall, rainfall variability, drought-prone areas, temperature (average, maximum and minimum), and the trend of rainfall and temperature over time and space. Similarly, soil quality parameters such as texture, soil organic carbon, slope/elevation, soil salinity, and soil displacement by water are mapped. Further, water resources and vegetation indices are mapped. Considering the major parameters of climate, soil, and water, a hotspot/suitability map of Morocco for wheat cultivation is developed. Remote sensing data such as Sentinel-2, Landsat-8, and MODIS satellites and the data sources such as FAO (soil salinity and soil organic carbon), ISRIC (soil parameters), and ESRI (10-m land use land cover) were used for mapping specific natural resources to identify hotspots of climatic parameters. This mapping work has provided a consolidated resource map which was scattered in different form and literature and also has identified a number of hotspots that requires due consideration for sustainable agriculture production.